2022
DOI: 10.3390/nano12122026
|View full text |Cite
|
Sign up to set email alerts
|

CsPb(Br/Cl)3 Perovskite Nanocrystals with Bright Blue Emission Synergistically Modified by Calcium Halide and Ammonium Ion

Abstract: Colloidal cesium lead halide (CsPbX3, X = Cl, Br, and I) perovskite nanocrystals (NCs) demonstrate supreme optical properties in the spectra region of infrared, red, and green. High-performance blue-emitting counterparts are still eagerly required for next-generation full-color displays. However, it is challenging to obtain efficient blue perovskite NCs, especially in a deep blue region with an emission wavelength of around 460 nm or shorter. Herein, calcium halide and ammonium ions are applied simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The incorporation of appropriate impurity ions into host lattices has been exploited as a promising method to stabilize the crystallographic phases while modulating the optical, electronic, and magnetic properties of diverse semiconductors [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Regarding the halide perovskites, the partial substitution of Pb 2+ by divalent metal ions, such as Cu 2+ , Mg 2+ , Fe 2+ , Co 2+ , Ni 2+ , and Mn 2+ at the B sites of the perovskite lattice have been demonstrated [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Klug et al revealed that the perovskite films retain an excellent photovoltaic performance if less than 3% Pb 2+ ions are substituted by homovalent metal species due to the high tolerance of the perovskite lattices [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of appropriate impurity ions into host lattices has been exploited as a promising method to stabilize the crystallographic phases while modulating the optical, electronic, and magnetic properties of diverse semiconductors [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Regarding the halide perovskites, the partial substitution of Pb 2+ by divalent metal ions, such as Cu 2+ , Mg 2+ , Fe 2+ , Co 2+ , Ni 2+ , and Mn 2+ at the B sites of the perovskite lattice have been demonstrated [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Klug et al revealed that the perovskite films retain an excellent photovoltaic performance if less than 3% Pb 2+ ions are substituted by homovalent metal species due to the high tolerance of the perovskite lattices [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Among them, the efficiency improvement of blue perovskite LEDs (PeLEDs) based on CsPbBr 3 is still inferior to that of their green and red counterparts. 14 The current approaches to achieve deep-blue emission are doping 15 and the Br/Cl mixed anion replacement 16,17 strategy. However, the devices usually have low device efficiency, short lifetime, and instability due to phase separation and ion migration.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the CsPbBr 3 nanostructures are extensively applied in solar cells, light-emitting diodes (LEDs), photodetectors, and other photovoltaic fields. , Among them, the efficiency improvement of blue perovskite LEDs (PeLEDs) based on CsPbBr 3 is still inferior to that of their green and red counterparts . The current approaches to achieve deep-blue emission are doping and the Br/Cl mixed anion replacement , strategy. However, the devices usually have low device efficiency, short lifetime, and instability due to phase separation and ion migration. In addition, ultra-small CsPbBr 3 quantum dots (QDs) with strong confinement can also achieve blue PeLEDs. , …”
Section: Introductionmentioning
confidence: 99%
“…Colloidal AgBiS 2 nanocrystal (NC), a member of the I–V–VI 2 ternary semiconductor materials [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], is a promising eco–friendly material for solar cells owing to colloidal AgBiS 2 NC having a wide absorption spectrum in the visible to near–infrared region (300–1600 nm) [ 8 , 9 , 10 ], high absorption coefficient (~10 5 cm −1 ) [ 1 , 11 , 12 , 13 ], and good air stability [ 8 ]. The hot injection method is widely used to prepare high quality NCs such as PbS [ 14 ], PbSe [ 15 , 16 ], and halide perovskite NCs [ 17 , 18 , 19 , 20 , 21 , 22 ]. In 2016, Bernechea et al synthesized colloidal AgBiS 2 NCs by the hot injection method using hexamethyldisilathiane (TMS) as the sulfur source and first reported colloidal AgBiS 2 NC–based solar cells with a certified power conversion efficiency (PCE) of 6.3% [ 1 ].…”
Section: Introductionmentioning
confidence: 99%